The Study of Occurrence of Organic, Infectious and Parasitic diseases in the Sheeps and Goats - Pramu Pramu (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Diseases in goats and sheeps often cause economic losses in the level of small farmers. This research aimed to study the incidence of the disease in the sheeps and the goats recorded at the Animal Health Laboratory STPP Magelang in 2011 to 2012. There were 132 incident cases of the disease in the sheeps and the goats over 12 months. Object of observation is STPP Magelang livestocks, livestocks owned by the assisted and unassisted ranchers. Research data from administrative records and laboratory covering the origins of livestocks, diseases history, clinical symptoms, laboratory results, treatment and post-treatment recording. Observations noted that there were 29, 26, 22, 15, 12, 9, 7, 5, 4 and 3 cases of bloat, diarrhea, nematodiasis, scabiosis, mineral deficiency, poisoning, orf, pink eye, myasis and others, respectively. The data were analyzed descriptively. Occurrence of bloat and diarrhea were observed more in the rainy season (P <0.05) than that of in the dry season and most of events were in the early season. Poisoning was more common in the dry season (P <0.05) than that of in the rainy season. Diarrhea was in the second order after bloating and tended to accompany other diseases. Nematodiasis treatment was often less effective. Although, positive nematode eggs were found during fecal examination, however, the hosts showed no clinical symptoms of parasitism. Pink eye and orf appeared in November. Mineral deficiency was not affected by the season, and its seasonal incidence(s) did not have any specific pattern. However, it tended to be appeared in every month. Recurrent scabiosis always occurred after the treatment. Percentage of high mortality occurred in bloating. Low incidence of the disease is endometritis and mastitis.Keywords: Goat, sheep, parasitic, infection, organic